Philosophy of education : (Routledge, 2009)
Foundations of Education helps aspiring teachers interpret the craft of teaching within the historical, philosophical, cultural, and social contexts of education inside and outside of schools. This volume contains substantial selections from those works widely regarded as central to the development of the field. These are the "essential texts" that lay the basis of further study for any serious student of education. The text is organized around the separate foundations disciplines—history, politics, sociology, philosophy— and includes extended selections from the works of John Dewey and W.E.B. DuBois to contemporary thinkers such as Maxine Greene and Diane Ravitch. Noted scholar and editor of this volume, Susan Semel, provides an introductory essay as well as questions for further discussion that contextualize the readings and highlight the selections’ continued importance and application to today’s most pressing educational issues.